eBook Mobile Payment Process Model - Shiratuddin, Norshuhada; Hassan, Shahizan; Zaibon, Syamsul Bahrin; Ab Salam, Sobihatun Nur (Information Science Reference, IGI Global, 2009)
Studies on the use of mobile payment (m-payment) method for buying electronic book (e-book) are very scarce, possibly not yet available. Consequently, a study was undertaken to accomplish the main aim of proposing an m-payment model for marketing and purchasing e-books. A number of process flow models are proposed to serve as diagrammatic representations of the process models that are of concerned. The models clearly specify all the entities involved, such as Telco, merchants, buyers, and e-book providers, and how the data and transactions, are flowing from one entity to another. The processes of browsing, buying, and downloading e-books are also documented. In validating the process flow models, two prototypes, a WAP and Web environments, were developed and tested to assess the model and system acceptance rating. Key findings indicate that m-payment is the most preferred payment method for buying e-book in higher learning institutions and the acceptance factors of such technology were found to be on the high and positive side.